KAJIAN EKONOMI PRODUK OLAHAN JAGUNG (STUDI KASUS) DI INDUSTRI RUMAH TANGGA KANAAN DI KELURAHAN TUAK DAUN MERAH KECAMATAN OEBOBO KOTA KUPANG - Cantika P Adu; Fredrik L Benu; Marthen Robinson Pellokila (Undana Press, 2020)
ABSTRACT The research conducted in home industry “Kanaan” in Tuak Daun Merah District of Oebobo Sub-district in Kupang City in July 2019 aims to the amount of revenue, cost of production, profit and loss reports and value added of the maize processing business in the “Kanaan” Home Industry. The determination of the research area was intentionally carried out (Purposive) and the research method used was the case study method. Primary data was collected through interviews, the collected data was analyzed descriptively, followed by an analysis of revenue, profit and loss account using the full-cost method and added value analysis. The results showed that the Kanaan home industry achieved an income of in July 2019 from each unit of production of 350 gr spicy fried corn in the amount of Rp27,300,000, - for 25 gr spicy fried corn in the amount of Rp23,520,000, while the balado fried corn in size 25 gr in the amount of Rp 11,760,000, - and for the profit of fried corn in the Canaan Home Industry in July 2019, namely 350 grams of spicy fried corn in the amount of Rp 17,174,226,- on the other hand25 grams of spicy fried corn in the amount of Rp 13,094,372, while the fried corn balado size of 25 gr amount to Rp5,684,699, - of processed corn products. The added value in July 2019 was Rp 13.242,-/kg with an added value of 51% for large-packed of spicy fried maize, an added value for small-packed of spicy fried maize was Rp 9,657-/kg with the added-value ratio of 43.11%, while the added value for small packaged of balado fried maize was Rp 8.857,-/kg with an added value ratio of 39.58%.